PENGGUNAAN STRATEGI THINK DALAM PEMBELAJARAN KOOPERATIF UNTUK MATERI BANGUN RUANG DI KELAS XII SMA NEGERI SIWALIMA AMBON - Novita Ivonne Choesni (Pattimura University, 2018)
Mathematics learning is generally done teacher-centered, while the 2013 curriculum based on constructivist demands are learner-centered learning. One learning model that is in accordance with the demands of the 2013curriculum is a cooperative learning model using theTHINK strategy. This study aims to develop cooperative learning devices using theTHINK strategy that is good for three dimension material, describes the effectiveness of cooperative learning by using theTHINK strategy for three dimension material, and comparing learning outcomes of students who take cooperative learning using the THINK strategy with students who follow conventional learning for three dimension material. The development of learning devices was carried out using the 4-D model Thiagarajan, et al. Which had been modified through a simplification process? The research data were analyzed descriptively. In addition, at the experimental stage, inferential ANAKOVA analysis was used. The results of the analysis show that (1) the learning devices produced, in the form of: learning plans, teacher manuals, student activity sheets, and learning outcomes tests, have met the criteria for good learning devices; (2) cooperative learning using the THINK strategyis effectiveused to teach three dimension material; (3) the learning outcomes of students who take cooperative learning using the THINK strategy  are better than the learning outcomes of students who take conventional mathematics learning.